The USE OF DIGITAL COMICS IN TORNADO MITIGATION FOR ELEMENTARY SCHOOL STUDENTS: Original Article - Hidayati, Nur; Kinasih, Raniah Lintang; Rokhman, Abdul (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Children are a vulnerable group in the face of disasters due to their age and limited knowledge. This study aims to analyze the impact of digital comic education on the preparedness of elementary school students in facing tornado disasters. The study was conducted using a quasi-experimental pre-test post-test with control group design on 90 elementary school students (46 in the intervention group and 44 in the control group). The intervention group received digital comics education (PDF), while the control group received education using PowerPoint media. Preparedness was measured using a questionnaire and tested using a paired t-test (α≤0.05). The results showed that 84.8% of elementary school students were in the less prepared category before intervention and increased to nearly prepared at 69.6% and prepared at 28.3% after education using digital comics. There was an impact of both digital comic and PowerPoint media education on increasing the preparedness of elementary school students (p=0.001; p=0.001) with an average mean increase of 11.46 and 7.89, respectively. There was a difference in post-test preparedness between the control and intervention groups (p=0.019). Digital comics proved to be more effective in increasing the preparedness of elementary school students in facing tornado disasters compared to PowerPoint media